Pengaruh Modifikasi Resep Lauk Nabati Diet Lunak terhadap Kesukaan dan Sisa Makanan Pasien RS D - Dhini Dhini; Sugiyanto Sugiyanto; Noor Jannah (Jurnal Surya Medika (JSM), 2022)
Background: Food acceptance is influenced by several factors, including the appearance of the food and the taste of the food. Food acceptance can be used as an indicator of success in providing food in hospitals and as a benchmark in achieving and fulfilling service standards. One of the efforts to achieve this success is through recipe modification, namely increasing the diversity of dishes, increasing the nutritional value of dishes, and increasing consumer acceptance of food. Objective: This study aims to determine whether there is an effect of modifying the recipe for soft diet vegetable side dishes on the preferences and food waste of patients at D Hospital. Method: Research in institutional nutrition with quantitative research with a quasi-experimental study. By using a group pre-test and post-test. The respondents of this study were patients with a soft diet at RS D. Results: there was an effect of modifying the recipe for the vegetable side dish of soft tempeh on the preference of the vegetable side dish of tempeh with a p-value (<0.05), namely: shape, serving, aroma, taste, and temperature, there was an effect of modifying the recipe for vegetable side dishes tofu soft diet on the preference for side dishes of vegetable tofu with p-value (<0.05), namely: color, presentation, seasoning, taste, and temperature. There was an effect of recipe modification on the remaining side dishes of soft diet tempeh with p = 0.001. There was no effect of recipe modification on the remaining side dishes of soft diet tofu with p = 0.204. Conclusion: there is the effect of modifying the recipe for the vegetable side dish of soft diet tempe on preference; there is the effect of modifying the recipe for the vegetable side dish of soft diet tofu on preference. There is an effect of modifying the vegetable side dish recipe on the leftovers, and there is no effect of modifying the tofu side dish recipe on the leftovers.